التصنيف الدولي للجامعات: قراءة في السياقات المفاهيمية - قاسمي, شوقي; سليماني, صباح (Sciences de l'Homme et de la Société, 2016)
تسعى هذه المقالة لمعالجة إشكالية التصنيف الدولي للجامعات، متخذة من التعريف بعناصر ومكونات أبرز النظم الحديثة لتقييم أداء مؤسسات التعليم العالي في العالم مادة للتحليل، معتمدة في ذلك على تناول متدرج، يبتدئ بتوضيح المعاني والدلالات المختلفة لمصطلح التصنيف الدولي للجامعات، مرورًا بالسياق التاريخي لنشأته وتطوره، ومن بعده العوامل الكامنة وراء بروز الحاجة إليه، وكذا تصاعد أهميته في الوسط الأكاديمي، وصولاً إلى استعراض مؤشرات وتفاصيل أربعة نماذج منه، بوصفها الأكثر ريادية ومصداقية في الأوساط الأكاديمية، والممثلة في: تصنيف شنغهاي، ملحق التايمز الأسبوعي (THES Q-S)، الويب ماتريكس، تصنيف التايمز، وانتهاءً بخاتمة تمثل ثمرة حركة فكرية تعبر عن منطق التحليل الذي التزم به عند هندسة هذه المقالة. Abstract : This article aims at overcoming the problematic issue of the international classification of universities .Defining the elements and the constituents of the major modern regimes to evaluate the performance of higher education institutions is at the heart of this subject's analysis. This article attempts to deal with the theme gradually. First, it starts with clarifying the copious meanings and connotations of the term “international classification of universities”. It moves then to the historical backgrounds of its evolution. After that, it discusses the reasons and the factors behind the necessity of having such categorization. It shows its significance in the academic millieu as it demonstrates the indicators and details of four of its samples. The latter are considered to be the top most credible ones .They are: Shenghahaii's grouping, the weekly Times’ THES Q-S, Web- matrix, and Times' grouping. This paper (piece) concludes with an account that expresses the intellectual movement which clears up the analytical logic we hold when we design this humble piece.